Internal Fixation of Displaced Intra-articular Fractures of the Hallux Through a Dorsomedial Approach: A Technical Tip - Nishikawa, Danilo Ryuko Cândido; Duarte, Fernando Aires; de Cesar Netto, Cesar; Monteiro, Augusto César; Albino, Rômulo Ballarin [UNESP]; Fonseca, Fabio Corrêa Paiva (SAGE Publications, 2018)
Phalangeal fractures of the toes represent common injuries of the forefoot. In the hallux, most fractures occur at the distal phalanx and frequently result from a direct crushing type of injury. Intra-articular fractures of the hallux are usually treated nonoperatively, except when the fragments are displaced and the joint is incongruent. Displaced fractures treated nonoperatively can result in degenerative arthritis of the interphalangeal joint, causing pain and range of motion limitation, hindering gait and weightbearing. The aim of this study was to present an option of operative approach in the treatment of displaced interphalangeal joint fractures of the hallux, along the medial border of the extensor hallucis longus tendon. It is our understanding that this approach minimizes injury to the soft tissue envelope, allowing a rigid fixation and early weightbearing and range of motion. Levels of Evidence: Level V: Expert opinion.
Keywords: big toe joint pain; diagnostic and therapeutic techniques; digital and sesamoid fractures; foot surgery techniques; forefoot